2022
DOI: 10.1007/s11104-021-05279-z
|View full text |Cite
|
Sign up to set email alerts
|

Balancing litterfall and decomposition in cacao agroforestry systems

Abstract: Backgrounds and aims Litter protects the underlying soil, depending on litterfall and decomposition, but dynamics of the standing litter stock in agroforestry systems remain poorly understood. We aimed to unravel effects of litter quality, temporal patterns, microclimate, and a possible home-field advantage (HFA) on standing litter dynamics across a land-use gradient. Methods We quantified litterfall, the standing litter stock, and microclimate during a ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 87 publications
0
6
0
1
Order By: Relevance
“…The conversion from tropical natural forest to monoculture plantation reduced annual litterfall production and caused a more pronounced seasonal pattern [103,108,109]. Yet, where the rate of litter decomposition is reduced by a low litter quality (high ratio of lignin plus polyphenolics over nitrogen) a continuous litter layer protecting the soil can nevertheless be achieved [110].…”
Section: Reduced Annual Litterfallmentioning
confidence: 99%
See 2 more Smart Citations
“…The conversion from tropical natural forest to monoculture plantation reduced annual litterfall production and caused a more pronounced seasonal pattern [103,108,109]. Yet, where the rate of litter decomposition is reduced by a low litter quality (high ratio of lignin plus polyphenolics over nitrogen) a continuous litter layer protecting the soil can nevertheless be achieved [110].…”
Section: Reduced Annual Litterfallmentioning
confidence: 99%
“…The litter production potential in a stand is positively correlated with soil organic matter content and soil fertility levels [111,112], although specific mechanisms that transfer organic matters from litter layers to the soil may require further study [110]. On the forest floor, litter buffers the nutrient supply, as immobilization and mineralization phases alternate [113].…”
Section: Reduced Annual Litterfallmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study of Vaupel et al (2023) in the glacier‐impacted North German Plain reported that intercropping patterns of two poplar species and black locust with crops favored the abundance, diversity, and functioning of the soil biota compared with monoculture cropland. On the other hand, decomposition processes of different woody and herbaceous litter largely influence the soil aggregation structure and are dominant drivers of soil nutrient cycling (Sari et al, 2022). Duran‐Bautista et al (2023) proposed significant differences in soil physical variables between agroforestry complex systems in the northwestern Colombian Amazon (Duran‐Bautista et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It can also indicate apparent contradictions that start with a mismatch of the taxonomic categories used. For example, various soil biota interacts with litter quality in maintaining a protective litter layer on the soil throughout the year (Sari et al 2022). In simple and multistrata coffee agroforestry systems in Indonesia these can include epigeic, endogeic, and anecic earthworms that differ in the soil layers where they are active (Hairiah et al 2006;Putri 2018), and thus in their functions as litter decomposer, and as a maker of horizontal and vertical soil pores.…”
Section: Introductionmentioning
confidence: 99%